(untitled) (Fiep Bulletin - online, 2015)
The present study aimes to ascertain the quality of life and health, as well as the incidence of muscle pain in the garbage men of Ponta Grossa, state of Parana. This research was conducted using two valid instruments for data collection: the diagram’s Corlett and Manenica and the questionnaire for assessing quality of life and health. The subjects who responded to the survey had an average age between twenty to forty years, and an the whole of a shift conducted the survey, finishing in forty employees with active participation and no abstention. The occupational risks present in the lives of those workers, because of the way they work, are massive. Given the many factors that can compromise the health of themselves, as direct contact with waste collected from domiciles, concerns about traffic, exhaustion, fatigue, solar radiation, exposure to climate change, noises, slopes and ground uphill, among other compromising factors. Is evident that the risk of injury, the type of work performed, are very big. Mostly due to run at a fast rhythm, causing greater stress on joints and spine. This way, check how it presents evidence of pain in some body segment of the garbage men, as well as their quality of life and health is what motivated this research to analyze the overview of the situation.